Three-Dimensional Printed Biomimetic Elastomeric Scaffolds: Experimental Study of Surface Roughness and Pore Generation - Daniele Marazzi; Federica Trovalusci; Paolo Di Nardo; Felicia Carotenuto (Biomimetics)
Tissue engineering is an emerging field within biomedicine, related to developing functional substitutes for damaged tissues or organs. Despite significant advancements, the development of effective engineering tissue constructs remains challenging, particularly when replicating elastic stretchability, which plays a critical role in many tissues. Therefore, the development of tough, elastomeric scaffolds that mimic the complex elasticity of native tissues, such as the myocardium, heart valves, and blood vessels, is of particular interest. This study aims to evaluate a flexible printable material (Formlabs’ Elastic 50A Resin V2) to develop porous 3D scaffolds using additive manufacturing stereolithography (SLA). The elastomeric samples were tested in relation to their swelling behaviour, mechanical properties, and exposure to low temperatures. Additionally, the effects of print orientation, water immersion, and exposure to low temperatures on surface roughness and porosity were investigated to determine the best conditions to enhance scaffold performance in biomedical applications. The results demonstrated that samples printed at 0°, immersed in water, and exposed to low temperature (−80 °C) showed a more uniform microporosity, which could improve the adhesion and growth of cells on the scaffold. This research highlights a practical and economical approach to enhancing elastomeric scaffolds, paving the way for improved outcomes in tissue engineering applications.